Small and large fiber neuropathy in adults with myotonic dystrophy type 1 - Solbakken, Gro; Løseth, Sissel; Frich, Jan C.; Dietrichs, Espen; Ørstavik, Kristin (Frontiers in Neurology, 2024)
Introduction Myotonic dystrophy type 1 (DM1) is an inherited neuromuscular disorder that affects multiple organs. In this study, we investigated symptoms of pain and presence of small and large fiber neuropathy in the juvenile and adult form of DM1. Method Twenty genetically verified DM1 patients were included. Pain was assessed, and neurological examination and investigations of the peripheral nervous system by quantification of small nerve fibers in skin biopsy, quantitative sensory testing and nerve conduction studies were performed. Results from skin biopsies were compared to healthy controls. Result Seventeen patients reported chronic pain. Large and/or small fiber abnormalities were present in 50% of the patients. The intraepidermal nerve fiber density was significantly lower in the whole group of patients compared to healthy controls. Conclusion Small-fiber neuropathy might be an important cause of pain in DM1.